Hubungan Kemampuan Manajemen Waktu dengan Tingkat Konsentrasi Belajar Santri Pengurus Asrama Pondok Pesantren Daarul Qur’an Putri Cikarang - Alya Fatiha Azzahra; Febri Dahlia; Putri Nurina (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This investigation aims to map the relationship between time management skills and the intensity of learning concentration possessed by the dormitory administrators at the Daarul Qur'an Putri Islamic Boarding School in Cikarang. By applying a quantitative approach with a correlational design, the entire population of 46 people was involved as respondents through a total sampling technique. Primary data was obtained through the time management scale instrument and the learning concentration scale, then processed using Pearson Product Moment correlation analysis. The results of data processing proved a significant positive correlation between the two variables with a value of r = 0.606 and p < 0.001. The magnitude of the coefficient of determination indicates that variations in learning concentration are influenced by time management skills by 36.7 percent, while the remaining 63.3 percent is triggered by other factors outside the limits of this study. This empirical evidence emphasizes that increasing skills in time management directly contributes to strengthening the learning concentration of dormitory administrators. These findings are expected to be a reference basis in developing guidance and counseling service strategies and designing more effective time management development programs in the Islamic boarding school environment.